Association of birth weight with risk factors of cardiovascular diseases: A birth cohort analysis from a rural area of Northern India - Divya Valecha; P. V. M. Lakshmi; Naresh Sachdeva; Rajesh Kumar (Wolters Kluwer Medknow Publications, 2022)
Background: Fetal origin of cardiovascular diseases (CVD) hypothesis has been explored mostly in retrospective studies. Objectives: A prospective study was conducted to find the association of birth weight with CVD risk factors. Methods: A cohort of 243 babies born in 1992-1993 in ten villages of Raipur Rani Block in India, were followed-up in 2016-2017. WHO STEPS methods were used to assess the risk factors of CVDs. A total of 213 (87.8%) participants were examined; blood samples were collected from 207. Multivariable regression analysis was done to adjust for the confounding variables. Results: Study participants were 22-24 year old, 27.7% were exposed to tobacco and 24.8% consumed alcohol, 3.3% were taking >5 servings of fruits and vegetables per day, 35.7% were physically inactive, 28.6% were overweight (body mass index [BMI] ≥23 kg/m2), 12.2% had hypertension, 16% had high cholesterol (≥200 mg/dl), 16.4% had insulin resistance (IR) (Homeostatic Model Assessment-IR >3), and 20.7% were born with low birth weight (<2.5 kg). Multivariable regression analysis revealed inverse relationship between birth weight and systolic blood pressure (regression coefficient ‒3.72 mmHg, 95% confidence interval ‒7.249; ‒0.183, P < 0.05). Conclusion: Birth weight has inverse relationship with blood pressure. Effect of birth weight on CVDs should also be studied in future follow-ups.